Understanding Restaurant Customers Environmental Behavior in the Social Media Context: An Application of Theory of Planned Behavior - Jang, Yoon Jung (Global business and finance review, 2022)
Purpose: This study tested the applicability of the TPB model to explaining restaurant customers' attitudes toward pro-environmental behavior supported in the social media community. The specific objectives were to identify the relative influence of each construct on behavioral intention and to investigate the moderating effect of economic/ social reward in the relationship between behavioral intention and environmental behavior. Design/methodology/approach: A survey was administered to U.S. restaurant customers, and for the main study, among the 240 surveys returned, 202 usable responses were chosen for final analysis. Multiple regression and hierarchical regression analyses were conducted to test research hypotheses. Findings: The results indicated that attitude, social norm, and perceived behavioral control were significant predictors in understanding customers' behavioral intention toward environmental activities promoted in the social media community. Hierarchical regression analysis demonstrated that economic and social reward moderate the relationship between behavioral intention and environmental behavior. Research limitations/implications: Because of incomplete examination in the social media context, future research should further test measurements of TPB constructs to confirm their validity and reliability. Originality/value: Since the influence of each construct of TPB model differ in different contexts, close examination in the social media context may contribute to further applications and extensions of the TPB model.